Surat Keputusan Bersama (SKB) Sebagai Langkah Penguatan Netralitas ASN Menuju Pemilu 2024 - Alikhan Salim; Tri Susilowati (Universitas Sains dan Teknologi Komputer, 2024)
In 2022, the government through the minister of state apparatus empowerment and bureaucratic reform, the minister of home affairs, the head of the state civil service agency, the chairman of the civil servant commission, and the chairman of the general election supervisory board signed a joint decree (SKB) concerning for the neutrality of civil servants in facing the 2024 elections. Reported by KASN, since December 2019, ASN violated was 528. In June 2020 the violations reached 369, exceeding half of the number in 2019. This research uses qualitative methods where the collection sourced from reviews of journals, books and others. Data analysis is carried out by trianggulation of content in order to produce objective and valid results. The results and analysis of the research are that there are four important factors in the implementation of the joint decree (SKB). First, communication is carried out creatively and innovatively. Second, resources are carried out by fulfilling qualifications and competencies for fosters and supervisors. Third, disposition is carried out by evaluating the effectiveness of sanctions that used. The four bureaucratic structures are made not only in the form of joint decisions, but continued by a work unit in the implementation of the policy.